Picosecond Avalanche Detector — working principle and gain measurement with a proof-of-concept prototype. (1st October 2022) - Paolozzi, L.; Munker, M.; Cardella, R.; Milanesio, M.; Gurimskaya, Y.; Martinelli, F.; Picardi, A.; Rücker, H.; Trusch, A.; Valerio, P.; Cadoux, F.; Cardarelli, R.; et al.
Abstract: The Picosecond Avalanche Detector is a multi-junction silicon pixel detector based on a (NP)drift (NP)gain structure, devised to enable charged-particle tracking with high spatial resolution and picosecond time-stamp capability. It uses a continuous junction deep inside the sensor volume to amplify the primary charge produced by ionizing radiation in a thin absorption layer. The signal is then induced by the secondary charges moving inside a thicker drift region. A proof-of-concept monolithic prototype, consisting of a matrix of hexagonal pixels with 100 μm pitch, has been produced using the 130 nm SiGe BiCMOS process by IHP microelectronics. Measurements on probe station and with a 55 Fe X-ray source show that the prototype is functional and displays avalanche gain up to a maximum electron gain of 23. A study of the avalanche characteristics, corroborated by TCAD simulations, indicates that space-charge effects due to the large primary charge produced by the conversion of X-rays from the ^55Fe source limits the effective gain.